HIGHER ORDER THINKING SKILL (HOTS) MATHEMATICS INSTRUMENT TEST BASED ON MACROMEDIA FLASH FOR JUNIOR SECONDARY SCHOOL STUDENTS IN BENGKULU CITY - Edi Susanto; Agus Susanta; Rusdi Rusdi (Universitas Bengkulu, 2020)
One of the demands of the output of students learning in junior secondary shool, especially in mathematics was the ability to think at a higher level. Some students still had difficulty in solving mathematical problems based HOTS because of students not familiar with the problems. So it was necessary to conduct training for mathematics teachers in preparing HOTS mathematical instruments and applying it in the form of computer-based tests using macromedia flash. The participants of the training were 30 secondary mathematics teachers the members of subject teachers forum (MGMP) that consisted of teachers of public and private junior scondary schools in Bengkulu City. The results of the training activities obtained 40 multiple choice questions from the results of the development of HOTS mathematical instruments. The instrument consisted of each 20 questions for grade VII and grade VIII. The participants' responses to the training showed that the increasing knowledge of the particpants, where the average knowledge of the participants was 35, and the post-test results showed that the increasing knowledge of the participants in preparing HOTS instruments with an average was 62.75. The results of the development of the instrument had met the criteria of valid, reliable, discrimination index, and difficulty levels. The 40 items of HOTS instruments that developed were applied in Macromedia flash software.